ANALISIS KESALAHAN SISWA PADA OPERASI HITUNG PECAHAN BERDASARKAN TINGKAT KECERDASAN SISWA - Rahmasantika, Danty; Prahmana, Rully (Universitas Papua, 2018)
Junior high school’s students should be able to determine fraction and alsoimplement the concepts of fraction to solve mathematics problem. However,in reality, so many mistake that occur for students in solving mathematicsproblem in the operation of fraction. The intelligence of students also affectsthe number of errors in solving the fractional counting operations. So, thepurpose of this study was to determine students' errors in solving the problemof fractional counting operations based on the level of students’ intelligence.This research is a descriptive qualitative research. The research results showthat the different category of students’ intelligent produce differentmathematical problem solving abilities. Students with low intelligencecategories make many errors in their completion. On the other hands, thestudent with high intelligence category make a few errors. DOI: https://doi.org/10.30862/jhm.v1i2.1041